2010
DOI: 10.1016/j.jmb.2010.08.030
|View full text |Cite
|
Sign up to set email alerts
|

The Metalloregulatory Zinc Site in Streptococcus pneumoniae AdcR, a Zinc-activated MarR Family Repressor

Abstract: Streptococcus pneumoniae D39 AdcR (adhesin competence repressor) is the first metal-sensing member of the MarR (multiple antibiotic resistance repressor) family to be characterized. Expression profiling with a ΔadcR strain grown in liquid culture (brain heart infusion; BHI) under microaerobic conditions reveals upregulation of 13 genes including adcR and adcCBA, encoding a high affinity ABC uptake system for zinc, and genes encoding cell-surface zinc-binding pneumococcal histidine triad (Pht) proteins and AdcA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
158
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(172 citation statements)
references
References 97 publications
(123 reference statements)
13
158
1
Order By: Relevance
“…In addition to genes encoding the Adc/Lmb system, we found a perfect AdcR box in the promoter region (400 bp upstream from the start codon) of 7 supplementary genes or operons (Table 3), in particular, upstream of the adh gene (sak_0087), encoding a potential zinc-containing alcohol dehydrogenase, which has already been identified to be a direct binding target of AdcR in S. pneumoniae (26,42).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…In addition to genes encoding the Adc/Lmb system, we found a perfect AdcR box in the promoter region (400 bp upstream from the start codon) of 7 supplementary genes or operons (Table 3), in particular, upstream of the adh gene (sak_0087), encoding a potential zinc-containing alcohol dehydrogenase, which has already been identified to be a direct binding target of AdcR in S. pneumoniae (26,42).…”
Section: Resultsmentioning
confidence: 85%
“…We have shown that the expression of the lmb, adcA, and adcAII genes is zinc dependent. Zn 2ϩ -dependent regulation is mediated in S. pneumoniae and S. pyogenes by the AdcR regulator (26,27,42). S. pneumoniae AdcR has a unique effector in zinc, and its crystal structure revealed the presence of two metal-binding sites (43).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S. pneumoniae encodes a homologous Zn 2ϩ uptake system (AdcABC) that is regulated by a ZitR homolog (AdcR) (76). AdcR also regulates the expression of the four pneumococcal histidine triad (Pht) proteins, PhtA, PhtB, PhtD, and PhtE (77), involved in surface adhesion, as well as the Zn 2ϩ -specific AdcA homolog AdcAII and a Zn 2ϩ -dependent alcohol dehydrogenase (78,79). The adc operon is present in most streptococci and has also been studied in Streptococcus gordonii, where it is involved in Mn 2ϩ homeostasis (80), and in Streptococcus suis, where it regulates the expression of a Zn 2ϩ /Mn 2ϩ uptake system, ribosomal genes, and pht genes (81).…”
Section: One-component Systemsmentioning
confidence: 99%
“…S. pneumoniae and Streptococcus suis AdcR proteins were then found to be DNA-binding proteins (1,3), and S. suis AdcR was shown to be a metalloregulator specifically binding the TTAACYRGTTAA palindrome (1). While this work was submitted for publication, the S. pneumoniae AdcR protein was characterized in both apo-and Zn(II)-bound forms, and three of its Zn(II)-binding residues were identified (44).…”
mentioning
confidence: 97%